Understanding the Decline in Marriage Rates in Indonesia: a Maqashid Asy-Syari'ah Analysis Using Jasser Auda’s Systems Theory - Zubaidah, Dwi Arini (STIS Ummul Ayman, Pidie Jaya, Aceh, Indonesia, 2025)
Marriage is an important event. In Indonesia, there has been a new trend among Indonesian young people towards postponing marriage. This is in accordance with BPS data, there is a decrease in the marriage rate during 2018-2023. This type of research is doctrinal legal research that a type of research that focuses on understanding and analyzing applicable legal regulations, legal doctrine, and legal rules. Research based on literature from law books, books, journals and the internet. The analysis of this research is based on maqashid asy syari'ah. This research produces several factors that have caused the decline in marriage rates in Indonesia, including: an increase in divorce, fear of the risk of divorce, changes in the mindset of the younger generation and their readiness for marriage. study of factors through the 5 features of Jasser Auda's maqashid asy syari'ah Islamic legal system theory, namely: cognitive character, comprehensiveness, openness, multidimensionality, and purposefulness. Marriage is the right of every human being with legal provisions that vary according to each person's circumstances.